The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1007/s10806-006-9019-4
|View full text |Cite
|
Sign up to set email alerts
|

An Ethical Toolkit for Food Companies: Reflections on its Use

Abstract: Nowadays many debates are going on that relate to the agricultural and food sector. It looks as if present technological and organizational developments within the agricultural and food sector are badly geared to societal needs and expectations. In this article we briefly present a toolkit for moral communication within the food chain. This toolkit is developed as part of a European research project. Next, we discuss what such a toolkit can bring about, given the characteristics of the present day agricultural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0
8

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 10 publications
(2 reference statements)
0
24
0
8
Order By: Relevance
“…Previous studies have indicated that there is limited understanding of the potential ecological effects of the application of ethical considerations (Deblonde et al, 2007;Dowd & Burke, 2013). Ecological problems have been connected to negative societal responses, even though attitudes toward the benefits of genetically modified (GM) foods may offset attitudes about its environmental risks (Dowd & Burke, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have indicated that there is limited understanding of the potential ecological effects of the application of ethical considerations (Deblonde et al, 2007;Dowd & Burke, 2013). Ecological problems have been connected to negative societal responses, even though attitudes toward the benefits of genetically modified (GM) foods may offset attitudes about its environmental risks (Dowd & Burke, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade there have been many public and private initiatives to improve standards and introduce food quality schemes in Europe (Deblonde, De Graaff, & Brom, 2007;Trienekens & Zuurbier, 2008). Business-to-consumer quality labels often communicate information on the country of origin, good manufacturing practices or production methods.…”
Section: Introductionmentioning
confidence: 99%
“…Today's consumers are more and more uncertain about how food companies really behave and how much are they socially responsible (Deblonde et al, 2007); the progressive globalisation of the food supply chain has generated uncertainty on safety and security practices; the consumption of mass food has addressed concerns about pandemic diseases (e.g. mad cow disease, foot and mouth disease, bird flu); the increasing awareness about the risks related to obesity has generated criticism of marketing and distribution practices; the use of genetically modified ingredients has raised the debate about how trustworthy is product labelling (MacDonald and Whellams, 2007) etc.…”
Section: Introductionmentioning
confidence: 99%
“…fair trade products, eco-compatibility). In this view, Business Ethics and CSR practices become a mean of competitive advantage for food companies (Deblonde et al, 2007).…”
Section: Introductionmentioning
confidence: 99%